Cross-cultural adaptation and validation of the Portuguese version of the metacognitive prospective memory inventory—short form (MPMI-s) in non-central nervous system cancer patients - Martins, Filipa Santos; Bártolo, Ana; Fernandes, Sara M.; Oliveira, Ana F.; Caetano, Ana Paula; Silva, Isabel S.; Rummel, Jan; Albuquerque, Pedro B.; Rodrigues, Pedro F. S. (Healthcare, 2025)
Background/Objectives: Cancer diagnosis and oncological treatments often lead to cognitive impairments, particularly in prospective memory, which affects the ability to recall future intentions. These difficulties can significantly impact therapeutic adherence, especially in the early stages of treatment, where timely medication and appointment adherence are critical. Despite this, effective measures for assessing prospective memory in cancer survivors remain limited. The current study aimed to translate and culturally adapt the Short Form of the Metacognitive Prospective Memory Inventory (MPMI-s) for use with Portuguese cancer survivors. Methods: The translation process involved back-translation, expert review, and pre-testing to ensure content validity. Psychometric evaluation was conducted with a sample of 111 cancer survivors [M(SD) = 49.3(9.4), ages 18-65], assessing internal consistency, factorial validity through principal components analysis, and convergent validity. Results: A final 18-item version of the MPMI-S demonstrated strong reliability and validity, comprising four factors: prospective forgetting, monitoring and planning strategies, imagery and visualization strategies, and external aid strategies. Significant correlations were found between these dimensions and traits such as conscientiousness, agreeableness, emotional stability, as well as distress and cognitive functioning. Conclusions: These findings underscore the potential of the MPMI-S as a valuable tool in clinical settings, offering insights not only into self-reported prospective memory abilities but also into the compensatory strategies employed by individuals in their daily routines. By integrating these aspects, this measure helps to identify key opportunities for rehabilitation aimed at minimizing the functional impact of the disease.